2017
DOI: 10.1042/bsr20170319
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine blocks TFAM degradation and up-regulates mitochondrial DNA copy number by interacting with TFAM

Abstract: The natural small molecule compound: 2,3,5,6-tetramethylpyrazine (TMP), is a major component of the Chinese medicine Chuanxiong, which has wide clinical applications in dilating blood vessels, inhibiting platelet aggregation and treating thrombosis. Recent work suggests that TMP is also an antitumour agent. Despite its chemotherapeutic potential, the mechanism(s) underlying TMP action are unknown. Herein, we demonstrate that TMP binds to mitochondrial transcription factor A (TFAM) and blocks its degradation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…It has been shown that mitochondrial function and subsequent cell growth and morphology can be compromised by TFAM gene knockdown, followed by reducing mtDNA copy number and expression (Jeng et al 2008). Consistent with previous studies, impaired TFAM expression negatively affected the mtDNA/nDNA (mitochondrial DNA per nuclear DNA copy number) ratio and mitochondrial respiratory chain efficiency (Wang et al 2001; Woo et al 2012; Xie et al 2016; Lan et al 2017). Decreased mitochondrial biosynthesis was shown by the mtDNA/nDNA ratio (Phillips et al 2014; Hsueh et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that mitochondrial function and subsequent cell growth and morphology can be compromised by TFAM gene knockdown, followed by reducing mtDNA copy number and expression (Jeng et al 2008). Consistent with previous studies, impaired TFAM expression negatively affected the mtDNA/nDNA (mitochondrial DNA per nuclear DNA copy number) ratio and mitochondrial respiratory chain efficiency (Wang et al 2001; Woo et al 2012; Xie et al 2016; Lan et al 2017). Decreased mitochondrial biosynthesis was shown by the mtDNA/nDNA ratio (Phillips et al 2014; Hsueh et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…For example, the experimental drug LY379268 was reported to upregulate the expression of TFAM and prevent diabetic peripheral neuropathy by improving mitochondrial function in dorsal root ganglion neurons (Chandrasekaran et al, 2017). In addition, etramethylpyrazine, a natural small molecule compound, was found to stabilize TFAM by directly interacting with TFAM, which blocked Lon protease access and thus decreased TFAM degradation (Lan et al, 2017). This metastasis-promoting effect of TFAM loss was strongly supported by both RNA-Seq and ATAC-seq, which showed that GO terms such as ECM remodeling, angiogenesis, cell migration, and adhesion were enriched.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin may be closely related to the PKA and ERK1/2 pathways (38)(39)(40), which play a key role in lipolysis (41). Melatonin can trigger PKA activation in the rodent malaria parasite, Plasmodium chabaudi (42).…”
Section: Discussionmentioning
confidence: 99%
“…This is the main route of fatty acid degradation and is closely linked to mitochondrial content and respiration capability (48). A previous study showed that an increase of PGC-1 promotes the expression of TFAM, an important regulator in mitochondrial biogenesis (40). TFAM translocates into the mitochondria to stimulate DNA replication and gene expression (49,50), thereby promoting mitochondrial biogenesis and function.…”
Section: Discussionmentioning
confidence: 99%